Computational Sustainability - Lässig, Jörg; Kersting, Kristian; Morik, Katharina (Studies in Computational Intelligence,, 2016)
The book at hand gives an overview of the state of the art research in Computational Sustainability as well as case studies of different application scenarios. This covers topics such as renewable energy supply, energy storage and e-mobility, efficiency in data centers and networks, sustainable food and water supply, sustainable health, industrial production and quality, etc. The book describes computational methods and possible application scenarios.